Association Between Job Stress and Organizational Commitment in Three Types of Chinese University Teachers: Mediating Effects of Job Burnout and Job Satisfaction - Wang, Peng; Chu, Pengpeng; Wang, Jun; Pan, Runsheng; Sun, Yu; Yan, Meng; Jiao, Longzhen; Zhan, Xiangping; Zhang, Denghao (Frontiers in Psychology, 2020)
Utilizing the Job Demands-Resources (JD-R) model as the theoretical framework, this study examines the relationship between job stress, job burnout, job satisfaction, and organizational commitment among 1,906 university teachers in China, and investigates teachers’ differences across groups. The result of SEM indicates that job burnout and job satisfaction could play mediating roles between job stress and organizational commitment. The result of multi-group analysis shows that for national university teachers, the positive effect of job stress on job burnout is the highest among three types of university teachers, the negative effect of job burnout on organizational commitment is lower compared with provincial university teachers and the negative effect of job burnout on job satisfaction is lower compared with provincial university teachers. Only for provincial university teachers, the job stress can significantly positively predict organizational commitment, and the independent mediating effect of job burnout is significantly greater than job satisfaction. The practical advice to enhance Chinese university teachers’ organizational commitment was provided in the end.